2023
DOI: 10.7554/elife.78512
|View full text |Cite
|
Sign up to set email alerts
|

Enteroendocrine cell lineages that differentially control feeding and gut motility

Abstract: Enteroendocrine cells are specialized sensory cells of the gut-brain axis that are sparsely distributed along the intestinal epithelium. The functions of enteroendocrine cells have classically been inferred by the gut hormones they release. However, individual enteroendocrine cells typically produce multiple, sometimes apparently opposing, gut hormones in combination, and some gut hormones are also produced elsewhere in the body. Here, we developed approaches involving intersectional genetics to enable selecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…The robust suppression of food intake in GIP-Dq mice was surprising in the light of recently reported contradictory findings using the same GIP-Cre strain in a genetic intersectional model that restricted hM3Dq expression to the intestinal epithelium [ 20 ], and led us to consider possible explanations for the discrepancy. One idea we considered was whether there might be a cell population in the CNS that was directly activated by CNO in GIP-Dq mice but not in the intersectional model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The robust suppression of food intake in GIP-Dq mice was surprising in the light of recently reported contradictory findings using the same GIP-Cre strain in a genetic intersectional model that restricted hM3Dq expression to the intestinal epithelium [ 20 ], and led us to consider possible explanations for the discrepancy. One idea we considered was whether there might be a cell population in the CNS that was directly activated by CNO in GIP-Dq mice but not in the intersectional model.…”
Section: Resultsmentioning
confidence: 99%
“…To enable chemogenetic stimulated secretion of GIP, GIP-Cre mice [ 21 ] were crossed with with Rosa26-fxSTOPfx-hM3Dq reporter mice [ 22 ] or with Vil1-p2a-FlpO & FL-hM3Dq positive mice, creating intestinally restricted (GIP-Dq INT ) hM3Dq expression [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enteroendocrine cells are scattered along the digestive tract, where they function in sensing various environmental stimuli and secrete neurotransmitters (such as serotonin, histamine, and glutamate) to regulate diverse biological and physiological processes. , Other neurotransmitters, including acetylcholine, norepinephrine, and GABA, regulate secretion in intestinal endocrine cells . Chemogenetic activation of different EEC subtypes variably impacts behavior and gut motility . Exposure to BPA increases the number of 5-HT-positive cells in pig small intestinal mucosa due to inhibition of serotonin (5-HT) production by enterochromaffin cells .…”
Section: Discussionmentioning
confidence: 99%
“… 26 , 27 There are at least 5 distinct EEC lineages defined by the expression of either ghrelin, glucose-dependent insulinotropic polypeptide, somatostatin, serotonin (enterochromaffin cells), or a combination of glucagon-like peptide 1, cholecystokinin, and/or neurotensin. 28 , 29 In human beings, genome-wide association studies have found EEC markers, including PHOX2B and UBE4A to be altered in specimens of terminal ileum from patients with Crohn's disease, 30 suggesting a role for EECs in colitis development. Alterations of enteroendocrine cell numbers and hormone secretion have been found in patients with inflammatory bowel disease and in animal models of colitis, 31 and previous investigators have explored the inflammatory and microbiologic triggers that induce EEC responses during intestinal inflammation.…”
mentioning
confidence: 99%